Hypoxia-guided adaptive radiation dose escalation in head and neck carcinoma: A planning study. (July 2015) - Servagi-Vernat, Stéphanie; Differding, Sarah; Sterpin, Edmond; Hanin, Francois-Xavier; Labar, Daniel; Bol, Anne; Lee, John A.; Grégoire, Vincent
Abstract Objective. To evaluate from a planning point of view the dose distribution of adaptive radiation dose escalation in head and neck squamous cell carcinoma (HNSCC) using 18F-Fluoroazomycin arabinoside (FAZA) positron emission tomography/computed tomography (PET-CT). Material/methods. Twelve patients with locally advanced HNSCC underwent three FAZA PET-CT before treatment, after 7 fractions and after 17 fractions of a carboplatin-5FU chemo-radiotherapy regimen (70 Gy in 2 Gy per fraction over 7 weeks). The dose constraints were that every hypoxic voxel delineated before and during treatment (newborn hypoxic voxels) should receive a total dose of 86 Gy. A median dose of 2.47 Gy per fraction was prescribed on the hypoxic PTV defined on the pre-treatment FAZA PET-CT; a median dose of 2.57 Gy per fraction was prescribed on the newborn voxels identified on the first per-treatment FAZA PET-CT; a median dose of 2.89 Gy per fraction was prescribed on the newborn voxels identified on the second per-treatment FAZA PET-CT. Results. Ten of 12 patients had hypoxic volumes. Six of 10 patients completed all the FAZA PET-CT during radiotherapy. For the hypoxic PTVs, the average D50% matched the prescribed dose within 2% and the homogeneity indices reached 0.10 and 0.12 for the nodal PTV 86 Gy and the primary PTV 86 Gy, respectively. Compared to a homogeneous 70 Gy mean dose to the PTVs, the dose escalation up to 86 Gy to the hypoxic volumes did not typically modify the dose metrics on the surrounding normal tissues. Conclusion. From a planning point of view, FAZA-PET-guided dose adaptive escalation is feasible without substantial dose increase to normal tissues above tolerance limits. Clinical prospective studies, however, need to be performed to validate hypoxia-guided adaptive radiation dose escalation in head and neck carcinoma.